Clinical monitoring of smooth surface enamel lesions using CP‐OCT during nonsurgical intervention. Issue 10 (9th March 2016) - Chan, Kenneth H.; Tom, Henry; Lee, Robert C.; Kang, Hobin; Simon, Jacob C.; Staninec, Michal; Darling, Cynthia L.; Pelzner, Roger B.; Fried, Daniel
Abstract : Introduction: Studies have shown that cross‐polarization optical coherence tomography (CP‐OCT) can be used to image the internal structure of carious lesions in vivo . The objective of this study was to show that CP‐OCT can be used to monitor changes in the internal structure of early active carious lesions on smooth surfaces during non‐surgical intervention with fluoride. Methods: Lesions on the smooth surfaces of teeth were imaged using CP‐OCT on 17 test subjects. Lesion structural changes were monitored during fluoride varnish application at 6‐week intervals for 30 weeks. The lesion depth ( Ld ), integrated reflectivity (Δ R ), and surface zone thickness ( S z ) were monitored. Results: A distinct transparent surface zone that may be indicative of lesion arrestment was visible in CP‐OCT images on 62/63 lesions before application of fluoride varnish. The lesion depth and internal structure were resolved for all the lesions. The overall change in the mean values for Ld, Δ R, and Sz for all the lesions was minimal and was not significant during the study ( P  > 0.05). Only 5/63 lesions manifested a significant increase in Sz during intervention. Conclusion: Even though it appears that most of the lesions manifested little change with fluoride varnish application in the 30 weeks of the study, CP‐OCT was able to measure the depth and internal structure of all the lesions including the thickness of the important transparent surface zone located at the surface of the lesions, indicating that CP‐OCT is ideally suited for monitoring lesion severity in vivo . Lasers Surg. Med. 48:915–923, 2016. © 2016 Wiley Periodicals, Inc.